The role of circular economy in achieving sustainable development goals: evidence from E7 countries - Li, Li (Technological and Economic Development of Economy, 2025)
Currently, the achievement of sustainable goals has now become obligation for economies due to uncertain economic situations at global level. Thereby, this prominent issue demands the focus at academia level. The study, in this regard, attempts to explore circular economy in view with sustainable development goals (SDGs) in the criteria of E7 nations. The study has used the level of investment, level of production and consumption, level of employment, and level of education to measure the circular economy of the country. The study has also used industrialization and inflation to predict sustainable development goals achievement as the control variable. The time span chosen for the is 2001–2020 and method of moment quantile regression (MMQR) approach has been used to evaluate the variables. Results revealed that the circular economy (level of investment, level of production and consumption, level of employment, and level of education), industrialization, and inflation are positively significant with SDGs achievement in E7 countries. The study helps the policymakers in formulating policies related to SDGs achievement by improving the circular economy in the country.First publihed online 06 June 2025